2002
DOI: 10.1037/0096-3445.131.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Separating sensitivity from response bias: Implications of comparisons of yes-no and forced-choice tests for models and measures of recognition memory.

Abstract: A fundamental challenge to psychological research is the measurement of cognitive processes uncontaminated by response strategies resulting from different testing procedures. Test-free estimates of ability are vital when comparing the performance of different groups or different conditions. The current study applied several sets of measurement models to both forced-choice and yes-no recognition memory tests and concluded that the traditional signal-detection model resulted in distorted estimates of accuracy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 47 publications
6
70
1
1
Order By: Relevance
“…Given the uneven distribution of response probabilities (odor was present on 75% of trials and absent on 25% of trials), d 0 could have been critically distorted by individual response bias (b; Kroll, Yonelinas, Dobbins, & Frederick, 2002). We therefore adjusted d 0 for variability in b, obtaining standardized scores.…”
Section: Discussionmentioning
confidence: 99%
“…Given the uneven distribution of response probabilities (odor was present on 75% of trials and absent on 25% of trials), d 0 could have been critically distorted by individual response bias (b; Kroll, Yonelinas, Dobbins, & Frederick, 2002). We therefore adjusted d 0 for variability in b, obtaining standardized scores.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some research suggests that the YN/2AFC relationship for discrimination is variable and depends on the stimuli and encoding conditions (Cook, Marsh, & Hicks, 2005). Further still, some research suggests that d'YN is an unreliable measure of discrimination and can lead to inflated measures of YN discrimination (Kroll et al, 2002). These latter two findings neither support the idea of equivalent discrimination between tasks nor the idea of superior 2AFC discrimination.…”
Section: Strengthcontrasting
confidence: 50%
“…Table 1). Other published studies have shown this trend (e.g., Kroll et al, 2002;Yonelinas et al, 1992).…”
Section: Yn Recognition Performancementioning
confidence: 67%
See 2 more Smart Citations